2020
DOI: 10.1159/000508997
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Effector and Memory Cellular Immunity in a Patient with Long-Term Complete Molecular Response to Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia

Abstract: This case report is about a patient who suffered from Philadelphia chromosome (Ph1)-positive acute lymphoblastic leukemia. The blasts were positive for myeloid-lineage markers including CD13 and CD33, as well as B-cell-lineage markers. Minor bcr-abl1 mRNA was detected by real-time quantitative polymerase chain reaction. Chromosomal abnormality monosomy 7 was also observed, in addition to Ph1. Despite treatment difficulties that were anticipated based on these findings, the patient had long-time complete molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Allogeneic donor lymphocyte infusion in patients with relapsed CML after allogeneic hematopoietic stem cell transplantation often shows effectiveness through cellular immunity [9]. In a previous study, we reported that long-lasting effector and memory CTLs with TCR clonality were detected in a patient with CP-CML who could achieve long-term survival with TKI-treatment-free remission and in a patient with Ph1-positive acute lymphoblastic leukemia with long-term complete molecular response [10, 11]. These effector and memory CTLs might play important roles in attacking leukemic stem cells and inhibiting regrowth.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Allogeneic donor lymphocyte infusion in patients with relapsed CML after allogeneic hematopoietic stem cell transplantation often shows effectiveness through cellular immunity [9]. In a previous study, we reported that long-lasting effector and memory CTLs with TCR clonality were detected in a patient with CP-CML who could achieve long-term survival with TKI-treatment-free remission and in a patient with Ph1-positive acute lymphoblastic leukemia with long-term complete molecular response [10, 11]. These effector and memory CTLs might play important roles in attacking leukemic stem cells and inhibiting regrowth.…”
Section: Discussion/conclusionmentioning
confidence: 99%